Service Quality Pada Perbankan Syariah Prespektif Maqashid Syariah Ibnu"ASYUR" - Syahrul Amsari; Dana Syahputra Barus; Sri Sudiarti; Marliyah Marliyah (Al-Buhuts, 2023)
Maqashid sharia is the main reference for maintaining social balance in society which is the basic goal of Islamic sharia. The author presents in simple terms the maqashid al-shari'ah theory according to Ibn Assyria's view. Points that are considered important in this issue include the definition of maqasid al-shari'ah, its content, and its implementation of Islamic banking. The low level of service quality provided by Islamic banking has resulted in a decrease in the level of customer trust, especially towards Islamic banking. Therefore, the author wants to examine the aspects of service quality which includes tangible, reliability, responsiveness, assurance and Empathy. This type of research is descriptive qualitative. Opinion of ibn Asyur which is considered in accordance with the Islamic Banking approach. Everything that contains the meaning of maintaining/maintaining the five maqasid al-shari'ah, is called mafsadah, rejecting/removing mafsadah means maslahah